Mediapolitical Discourse: Concepts and Framework - N. V. Stepanova; E. V. Kurganskaia (Дискурс, 2024)
Introduction. The article presents the results of the review of scientific works on discourse theory, reflecting the stages of evolution of media-political discourse in Russian linguistics. The aim of the article is to summarize, systematize and analyze approaches to the study of media-political discourse and concepts of its comprehension. Such concepts as media discourse, media text, media linguistics, and political discourse are considered.Methodology and sources. The article is prepared in the context of the cognitive-discursive paradigm, functional approach to discourse analysis, and media linguistics. In accordance with the postulates of critical discourse analysis, media-political discourse is considered as a constitutive of social practice. The main research method is an analytical scientific review of works on discourse theory.Results and discussion. In the course of the review of works on media and political discourse the main approaches to the understanding and research of media-political discourse are highlighted. The boundaries of this type of discourse as one of the areas of modern discourse theory are outlined. The concepts of scientific cognition that conditioned the formation of media-political discourse are identified. A review of works on related types of discourse at the previous stages of scientific thought is given. Internet discourse is viewed as an alternative source of political information. The article emphasizes the elements of language of enmity and the binary opposition “us/them” in the media-political discourse.Conclusion. The paper reveals a tendency to merge media discourse and political discourse within the framework of media-political discourse in modern linguistics. Among the key approaches to the study of media-political discourse the following approaches are identified: cratological, structural-communicative and media-technological ones; when analyzing the blogosphere it is advisable to refer to critical discourse analysis, structuralfunctional and comparative approaches. The most promising areas of the research include the identification of the essential characteristics of media-political discourse, and the development of genre stratification of this type of discourse.